Highly Promiscuous Oxidases Discovered in the Bovine Rumen Microbiome - Ufarté, Lisa; Potocki-Veronese, Gabrielle; Cecchini, Davide; Tauzin, Alexandra S.; Rizzo, Angeline; Morgavi, Diego P.; Cathala, Bernard; Moreau, Céline; Cleret, Megane; Robe, Patrick; Klopp, Christophe; Laville, Elisabeth (Frontiers in Microbiology, 2018)
The bovine rumen hosts a diverse microbiota, which is highly specialised in the degradation of lignocellulose. Ruminal bacteria, in particular, are well equipped to deconstruct plant cell wall polysaccharides. Nevertheless, their potential role in the breakdown of the lignin network has never been investigated. In this study, we used functional metagenomics to identify bacterial redox enzymes acting on polyaromatic compounds. A new methodology was developed to explore the potential of uncultured microbes to degrade lignin derivatives, namely kraft lignin and lignosulfonate. From a fosmid library covering 0.7 Gb of metagenomic DNA, three hit clones were identified, producing enzymes able to oxidise a wide variety of polyaromatic compounds without the need for the addition of copper, manganese or mediators. These promiscuous redox enzymes could thus be of potential interest both in plant biomass refining and dye remediation. The enzymes were derived from uncultured Clostridia, and belong to complex gene clusters involving proteins of different functional types, including hemicellulases, which likely work in synergy to produce substrate degradation.